PELATIHAN PEMBUATAN SISTEM INFORMASI SEKOLAH BERBASIS WEB KEPADA GURU SMA ISLAM MADINATUL ULUM - TANGERANG: PELATIHAN PEMBUATAN SISTEM INFORMASI SEKOLAH BERBASIS WEB KEPADA GURU SMA ISLAM MADINATUL ULUM - TANGERANG - Yonathan; Suparli; Sutriyono; Rizal Alfan Fahmi; Ai Nuril Aini; Ikhsannudin Ma’sum; Wildan Hilmi Mubarok; Zakaria Levi; Alexander Diaz; Yehezkiel Chandra; Elni Agustiana Ali (CV. Multi Kreasi Media, 2022)
The development of Information and Communication Technology in the 21st century is very fast. Along with thedevelopment of the industrial revolution 4.0, current internet technology can reach all levels of society, whether by individuals,communities, government agencies, educational institutions or companies. With the development of information technologytoday, all transaction processes can be transferred to digital, especially during a pandemic like today, all information can betransformed digitally through the website. Currently, there are many methods of creating websites, either fundamentally orinstantly through available platforms, such as WordPress or Blogspot. In order to provide understanding to teachers andstudents at SMA Islam Madinatul Ulum Sukadiri Banten, we students and students at the University of Pamulang, InformaticsEngineering Study Program, held training on making a website-based school information system. With this activity, it is hopedthat teachers and students at SMA Islam Madinatul Ulum - Tangerang can create or develop a website for school informationsystems, or personal needs.